Harry Dinosaurs Say Raah - Ian Whybrow (London Gullane Children's Books, 2002)
In the third book about Sammy, a young boy takes his toy dinosaurs with him to help calm his fears on his first visit to the dentist.
Keywords: Read Aloud + PY-UOI - Who we are -- Read Aloud + PY-UOI - Who we are; Healthy Lifestyle